Evaluating the effectiveness and implementation of an online professional development program for health professional educators: The case of Jimma University - Tadesse, Tefera; Yimer, Endris Mekonnen; Hailu, Addisalem Taye; Gedamu, Shewatatek (Bahir Dar Journal of Education, 2024)
The usage of virtual platforms for reforming teachers’ continuous professional development (CPD) is becoming more and more necessary in contemporary higher education (HE) settings. For a comprehensive understanding of the implications of this strategy for CPD, research studies from various contexts are required. This study evaluated the effectiveness and implementation of a pilot online professional development (PD) package called the â€˜higher diploma program (HDP)â€™ for health professional educators (HPEs) in the Ethiopian HE context. We used mixed methods in a Hybrid II design. Additionally, a comprehensive e-learning quality framework guided the overall research and integration of the qualitative and quantitative data. The qualitative component includes a key-informant interview (KII) with facilitators, a program coordinator, and a single focus group discussion with HPEs. Additionally, the quantitative component includes a cross-sectional survey of the (HPEsâ€™) responses to a self-report questionnaire. The findings show that this pilot project was feasible and well accepted by the HPEs, facilitators, and coordinators of the project. These participants also perceived several implementation challenges as weaknesses of the pilot project. Mitigating the prevailing challenges requires sustained and collaborative efforts by universities, the education and health sector, and other partner institutions. Our interpretations imply that customizing online PD in HE is, ultimately, a local phenomenon that results from individual motivation and interest, institutional capacity, and contextual factors like access to technology, the quality of online PD resources, and program management.